A revised genus-level classification for Cerrenaceae (Polyporales, Agaricomycetes) - O. Miettinen; J. Vlasák; E. Larsson; J. Vlasák Jr; J.S.S. Seelan; Hernawati Nasir; Q. Levicky; K.-H. Larsson; V. Spirin (ResearchGate, 2023)
Cerrenaceae is a small family of polypores and hydnoid fungi in the order Polyporales (Basidiomycota). The family consists of white-rot fungi, some of which are serious tree pathogens. Combining morphological evidence with a phylogenetic dataset of six genetic markers, we revise generic concepts in the family and propose a seven-genus classification system for the family. Two genera are introduced as new: the monotypic Acanthodontia for Radulodon cirrhatinus, and Lividopora for the Rigidoporus vinctus complex. We re-introduce the name Somion for the Spongipellis delectans complex. Other recognized genera in the family are Cerrena, Irpiciporus, Pseudolagarobasidium, and Radulodon. New species introduced are Irpiciporus branchiformis from Tanzania, Lividopora armeniaca, and L. facilis from Southeast Asia, and Somion strenuum from East Asia. We provide nomenclatural comments on all the names combined to the above Cerrenaceae genera and typify Cerrena unicolor, C. zonata, Polyporus carneopallens (= L. vincta), Somion occarium, and S. unicolor. The genus Hyphoradulum belongs to Cystostereaceae (Agaricales), and we transfer the type species H. conspicuum to Crustomyces. Our study highlights the importance of integrating different basidiocarp types in analyses when revising genus classification in macrofungi.